Dynamics of viral load and anti-SARS-CoV-2 antibodies in patients with positive RT-PCR results after recovery from COVID-19 - Song, Kyoung-Ho (Korean J Intern Med, 2021)
Recently, the number of patients with coronavirus disease 2019 (COVID-19) who have tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), via the reverse transcription polymerase chain reaction (RT-PCR) test, after recovery has increased; this has caused a dilemma regarding the medical measures and policies. We evaluated the dynamics of viral load and anti-SARS-CoV-2 antibodies in four patients with positive RT-PCR results after recovery. In all patients, the highest levels of immunoglobulin G (IgG) and IgM antibodies were reached after about a month of the onset of the initial symptoms. Then, the IgG titers plateaued, and the IgM titers decreased, regardless of RT-PCR results. The IgG and IgM levels did not increase after the post-negative positive RT-PCR results in any of the patients. Our results reinforced that the post-negative positive RT-PCR results may be due to the detection of RNA particles rather than reinfection in individuals who have recovered from COVID-19.